Evaluation of the Ab-Dtpa Multiextractant in Chilean Soils of Different Origin with Special Regard to Available Phosphorus - Escudey-Castro, A; Escudey-Castro, A (2012)
The objective of this study was to evaluate the suitability of the ammonium bicarbonate diethylenetriaminepentaacetic acid (AB-DTPA) multiextractant to estimate the available P, exchangeable cations (K, Ca, Mg, Na) and extractable micronutrients (Cu, Fe, Mn, Zn) in comparison with conventional soil tests (Olsen-P, NH4OAc-exchangeable cations and DTPA-extractable micronutrients) in alkaline, acidic and volcanic acidic soils (n = 50). Exchangeable cations and extractable micronutrients were determined in soil extracts by ICP-OES. Phosphorus was determined colorimetrically in Olsen extracts, while in AB-DTPA extracts, P was determined both colorimetrically (AB-DTPAC-P) and by ICP-OES (AB-DTPAICP-P). In 14 soils, the available soil and plant P were determined in a pot experiment with ryegrass (Lolium multiflorum L). Both the AB-DTPAC-P and AB-DTPAICP-P were highly correlated with Olsen-P in alkaline and acidic soils. All P extractants were highly correlated with plant P concentration and uptake, but in soils with Olsen-P <20 mg kg-1 the AB-DTPA-P showed weaker relationships with P availability. The AB-DTPA method can be recommended to estimate the available P in alkaline and acidic soils, excluding Andisols, which typically contain very low amounts of available P. For K, Mg, Na, Cu, Fe, Mn and Zn, the multiextractant was highly correlated with respective conventional tests in all soils. © 2012 Copyright Taylor and Francis Group, LLC.